Modeling the spread of bed bug infestation and optimal resource allocation for disinfestation - Ali Gharouni; Lin Wang (Mathematical Biosciences and Engineering)
A patch-structured multigroup-like $SIS$ epidemiological model is proposed to study the spread of the common bed bug infestation.It is shown that the model exhibits global threshold dynamics with the basic reproduction number as the threshold parameter.Costs associated with the disinfestation process are incorporated into setting up the optimization problems.Procedures are proposed and simulated for finding optimal resource allocation strategies to achieve the infestation free state.Our analysis and simulations provide useful insights on how to efficiently distribute the available exterminators among the infested patches for optimal disinfestation management.